1997
DOI: 10.1590/s0074-02761997000500013
|View full text |Cite
|
Sign up to set email alerts
|

Acute Schistosomiasis: Report on Five Singular Cases

Abstract: The cases of five patients with unusual manifestations of acute schistosomiasis mansoni are described in this paper. One patient developed skin lesions, three displayed diverse lung involvement, and one presented pyogenic liver abscesses caused by Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
0
31
0
2
Order By: Relevance
“…The difficulties in establishing the diagnosis of acute schistosomiasis mansoni, especially before the appearance of eggs in the faeces, are well known (Neves 1992, Rabello 1995, Lambertucci 1997. In the collected data, this fact was expressed by three occurrences: firstly, the number of medical facilities searched per patient.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in establishing the diagnosis of acute schistosomiasis mansoni, especially before the appearance of eggs in the faeces, are well known (Neves 1992, Rabello 1995, Lambertucci 1997. In the collected data, this fact was expressed by three occurrences: firstly, the number of medical facilities searched per patient.…”
Section: Discussionmentioning
confidence: 99%
“…This acute form of the disease was first described in Japan over 100 years ago, yet it remains the least known of all the clinical stages of schistosomiasis. Percutaneous penetration of the cercariae can provoke a temporary urticarial rash that can manifest within hours and persist for days as maculopapular lesions (8,111,164,165,190,225). In temperate climate zones, a similar "swimmers itch" is also frequently seen with avian trematode cercariae (23).…”
Section: Pathology and Clinical Outcomes Acute Diseasementioning
confidence: 99%
“…5 Hepatic hydatid cysts (Ecchinococcus granulosus) also become secondarily infected. 6 In addition, migrating Ascaris lumbricoides 7,8 and, more recently, acute schistosomiasis [9][10][11] have been implicated as predisposing factors in the genesis of pyogenic liver abscess.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and experimental study demonstrated that acute schistosomiasis concurrent with S. aureus bacteremia favors the colonization of the liver by bacteria causing pyogenic liver abscesses. [9][10][11] The following aspects of the pathogenesis of the pyogenic liver abscess in mice infected with Schistosoma mansoni are evaluated herein: a) the role of the eggs of S. mansoni in the genesis of the abscesses; b) the influence of the acute and chronic phases of schistosomiasis in the development of the abscesses; and c) the effect of schistosomiasis treatment on the development of the abscesses.…”
Section: Introductionmentioning
confidence: 99%